TEACHERS' PERSPECTIVES ON THE USE OF UNDERSTANDING BY DESIGN (UBD) IN SECONDARY SCHOOL LESSON PLANNING: PERSEPSI GURU TERHADAP PENERAPAN UNDERSTANDING BY DESIGN (UBD) DALAM RANCANGAN PEMBELAJARAN DI SEKOLAH MENENGAH - Retnowati, Nanik (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
This study aims to analyze teachers' perspectives on the implementation of the Understanding by Design (UbD) framework in lesson planning at the junior and senior high school levels. A qualitative design method with an inductive analysis approach was used in this study. Data were collected through semi-structured interviews with seven participants, all of whom are English language teachers at the junior and senior high school levels. The findings reveal that the majority of teachers have a good to very good understanding of the UbD and Backward Design concepts, with only one respondent showing a low level of understanding. Most of the teachers have implemented UbD in their teaching practices and demonstrate a high commitment to self-development in applying UbD. However, two respondents reported a moderate level of self-development. These findings indicate that teachers are relatively familiar with the basic concepts of UbD, but challenges remain in ongoing professional development. This study suggests the need for more intensive support and continuous training to maximize the implementation of UbD in the classroom.